ABOUT MATHEMATICAL MODELLING OF INFLUENCE OF STEAM PRESSURE UPON SOIL - G. E. Agakhanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
For the water-saturated two-phase soil environment with the properties changing in time within a continuous isotropic body with linearly - hereditary creep executed mathematical modeling of influence of steam pressure upon soil. The new settlement model in which the steam pressure upon soil is considered as impact of the compelled deformations is developed. It is shown that the developed and known settlement models (in known model the steam pressure upon soil is considered as action of volume forces) will completely be coordinated with the general conditions of equivalence of influences established earlier in mechanics of a deformable solid body. Special cases of the soil environment are considered.